The illusion of the Oracle: : Tragedy in the Colonial Wars. Algiers 1961, Kabul, 2021. - Álvarez, José Maurício (Advances in Social Sciences Research Journal, 2021)
Abstract The familiar face of empires is external intervention as opposed to local culture. We follow Michel Onfray's thesis about the oracular illusion when one more individual or country tries to avoid the fulfillment of a nefarious prediction, which materializes as a catastrophe. Algeria conquered in 1830 was incorporated into French territory. In 1954 the FLN rebelled, and in 1961, General Charles de Gaulle negotiated the independence of Algeria, causing the disastrous departure of 750,000 French settlers and the death of French supporters. From 1962 to 2021, the withdrawals of imperial powers from their colonies, France from Algeria, the United States in Afghanistan, resulted in catastrophes and uncertainties. The imperial power of the United States aimed to defeat its bipolar antagonist, the USSR when it invaded Afghanistan. They conducted an inconsequential policy to beat their rival, arming and financing the Taliban's victorious resistance, the freedom fighters. The oracular illusion led the United States to support the future antagonist, Islamic fundamentalism, destined for the world caliphate. After the departure of the USSR, American power despised the Taliban, who harbored al Qaeda, leading to 9/11. In 2001 the United States invaded Afghanistan and abandoned it after 20 years of war without the precaution of obtaining plans or safeguards for the government in Kabul. After the disastrous retreat, the victorious Taliban demonstrated, like the FLN in Algeria, the fulfillment of the oracular illusion.